PENGARUH PENGGUNAAN GEOGEBRA SEBAGAI MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATERI FUNGSI KUADRAT DI KELAS X SMA N 10 MEDAN T.A 2024/2025 - Ceri E Siregar; Samuel Juliardi Sinaga; Ruth M. Simanjuntak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of GeoGebra media on students' learning motivation in quadratic functions. The research method used was quantitative research with a correlational approach. The population was all 10th grade students of SMA N 10 Medan. The instruments used by the researcher were a learning motivation questionnaire and a student ability test. The results showed that the use of GeoGebra as a learning medium had an effect on students' learning motivation. Based on the statistical analysis, the sig (2-tailed) value was 0.008 < 0.05 with a significance level of 5%. This means that α0 is rejected and α is accepted. Based on the results of the simple regression test, the regression equation Y = 77.283 + 0.999X was obtained. Based on the results of the regression significance test, it can be concluded that variable X has a significant effect on Y.